Voxel-based analysis and multivariate pattern analysis of diffusion tensor imaging study in anti-NMDA receptor encephalitis. - Liang, Yanli; Cai, Luhui; Zhou, Xia; Huang, Huanjian; Zheng, Jinou (Neuroradiology, 2020)
Purpose: This study aimed to investigate brain white matter (WM) changes and their relationship to cognition in patients with anti-N-methyl-D-aspartate (anti-NMDA) receptor encephalitis. Multivariate pattern analysis (MVPA) was used to explore brain regions that play an important role in classification. Methods: Fifteen patients and fifteen controls underwent Montreal Cognitive Assessment (MoCA) and diffusion tensor imaging. Based on fractional anisotropy (FA) and mean diffusivity (MD) for MVPA classification, the weights of each brain region were calculated. Results: Compared with the controls, the patients showed an FA reduction in right middle temporal gyrus, left middle cerebellar peduncle, right praecuneus, and an MD increase in left medial temporal gyrus and left frontal lobe. The MoCA score for patients was lower than controls, especially in executive function, fluency, delayed recall and visual perception items. The FA value of right praecuneus was positively correlated with total MoCA score and fluency score. The MD of left frontal lobe was negatively correlated with total MoCA score, and MD of the left medial temporal gyrus was positively correlated with delayed recall. The accuracy, sensitivity and specificity of classification based on FA were 70%, 60% and 80%, respectively. Based on MD, they were each 80%. The brain regions with large weights from FA and MD overlap in temporal lobe, cerebellum and hippocampus. Conclusions: These results suggest that WM changes are associated with cognitive deficits. MVPA based on FA and MD has good classification ability. Our study may provide new insights into the pathophysiological mechanisms of residual cognitive deficits.